Exploring the Persistent Reading Difficulties of Elementary Learners - Villa, Christian Sharmaine (International Journal of Sustainability and Advanced Integrated Research, 2026)
Persistent reading difficulties remain a significant concern in elementary education because they affect learners’ academic performance, motivation, confidence, and participation in school activities. This study explored the meanings attached to persistent reading difficulties and the factors contributing to their persistence among elementary learners in the Bangui–Dumalneg District. Guided primarily by Rosenblatt’s Transactional Theory of Reading and supported by the Simple View of Reading and Vygotsky’s Sociocultural Theory, the study employed a qualitative, interpretive research design. Data were gathered through semi-structured interviews and focus group discussions involving 46 participants, including struggling readers, parents or guardians, teachers, and school heads. Purposive sampling was used to select participants with direct experience related to persistent reading difficulties, and data were analyzed using thematic analysis. Findings revealed that learners associated reading difficulties with embarrassment, dependence, and reduced confidence; parents viewed them as a challenge accompanied by hope and concern; teachers regarded them as instructional and professional challenges; and school heads perceived them as school-wide concerns requiring coordinated action. The persistence of reading difficulties was attributed to repeated failure, loss of confidence, limited practice and guidance, avoidance of reading situations, inconsistent home support, instructional constraints, and systemic limitations within schools. The study concluded that persistent reading difficulties are shaped by interacting emotional, social, instructional, and institutional factors rather than by skill deficits alone. It recommends strengthening home–school collaboration, providing sustained literacy support, and addressing contextual factors that influence reading development. The study aligns with Sustainable Development Goal (SDG) 4 on Quality Education by promoting inclusive and equitable learning opportunities through improved literacy support. It also supports SDG 10 on Reduced Inequalities by highlighting barriers that affect learners’ access to quality literacy development. The findings contribute to educational, community, and institutional sustainability by informing literacy practices, stakeholder collaboration, and school-based interventions that support long-term learner development.